PENGARUH KOMPETENSI PROFESSIONAL DAN FASILITAS BELAJAR TERHADAP MUTU PROSES PEMBELAJARAN PADA SATUAN PENDIDIKAN SD NEGERI DI DESA CIBATOK - Rahmawati, Ima; Aviyana, Vina; Lestari, Hana; Dafenta S, Hadi (JURNAL KAJIAN ISLAM MODERN, 2023)
Education is something that is inherent in human life and is the hope for a world of education so that it can give birth to generations of quality, morality, innovation, creativity and ability to compete in the future. The birth of this quality generation must of course be supported by professional competence and supporting school facilities so if everything is fulfilled then a success in the quality of the learning process will be achieved. This study aims to determine the effect of professional competence and learning facilities on the quality of the learning process in public elementary school education units in Cibatok village. This research is a type of quantitative research with survey research methods to determine the effect of variables and to test several hypotheses. The data collection techniques in this study used non-test techniques, namely to obtain information or data needed by researchers. With primary data collection techniques and secondary data, for example, such as distributing questionnaire instruments. The results of this study state that professional competence and learning facilities have a significant effect on the quality of the learning process. This is evidenced by the probability value of Sig. obtained by 0.000 <0.05, so it can be concluded that there is a significant influence between the variables of professional competence (X1) and learning facilities (X2) together on the quality of the learning process (Y). So it can be interpreted that these two factors can improve the quality of the learning process.